Occurrence of Acetaminophen, Amoxicillin, Diclofenac and Methylparaben in Lagos and Ologe Lagoons, Lagos, Nigeria - O.S. Folarin; A.A. Otitoloju; N.H. Amaeze; J.K. Saliu (Journal of Applied Sciences and Environmental Management)
The occurrence of acetaminophen, amoxicillin, diclofenac and  methylparaben in Lagos and Ologe Lagoons was investigated by random sampling of the water bodies during rainy and dry seasons. Samples analysis was carried out using high performance liquid chromatography. For the two seasons, the mean environmental concentrations of acetaminophen in Lagos and Ologe Lagoons were 0.075 μg/L and 1.233 μg/L respectively. The mean environmental concentration of amoxicillin in Lagos Lagoon was 0.008 μg/L while 0.003 μg/L was the mean value in Ologe Lagoon. Diclofenac occurrence in Lagos Lagoon had a mean value of 0.136 μg/L while 0.519 μg/L was recorded in Ologe Lagoon. The environmental concentration of methylparaben in Lagos Lagoon was 0.453 μg/L while its means concentration in Ologe Lagoon was 0.089 μg/L. From the results, the environmental concentrations of acetaminophen and diclofenac in Ologe Lagoon were higher than their level of occurrence in Lagos Lagoon. However, the levels of occurrence of amoxicillin and methylparaben in Lagos Lagoon were higher than their environmental concentrations in Ologe Lagoon. Methylparaben was the most frequently detected in the water bodies with 87.5% detection frequency. This was followed by diclofenac with 75%. Also, 50% of the water samples analysed contained acetaminophen while amoxicillin had the least (37.5%) frequency of occurrence. The study established that there are active pharmaceuticals compounds and excipients present in the Nigerian aquatic environment which are  micropollutants of emerging environmental concerns and of significant ecological risk. Therefore, there is need for environmental regulators to make concerted efforts towards environmental monitoring of this group of pollutants.